Методи захисту від найпоширеніших загроз wi-fi мережам - Зозуля, А. С.; Медведєв, Є. О. (ХНУРЕ, 2024)
Unauthorized access to Wi-Fi networks provides hackers with the ability to intercept sensitive information such as passwords, credit card numbers, or per sonal data transmitted over the network. The theses discuss the main types of attacks on Wi-Fi networks and provide recommendations for minimizing the success of such attacks.
Keywords: загрози wi-fi мережам; захист від загроз мережам